The Relationship Between Time Management and Work–Family Conflict Among Married Female Nurses at Sekayu Regional Public Hospital - Hidayati, Intan Asharin; Rina Oktaviana (JIPSI Jurnal Ilmiah Psikologi, 2026)
This study aims to examine the relationship between Time Management and Work–Family Conflict among married female nurses working at Sekayu Regional Public Hospital. The sample consists of 128 respondents selected using a total sampling technique. Data were collected using two research instruments measuring Time Management and Work–Family Conflict. The instruments were tested for validity and reliability prior to hypothesis testing. The results of the validity test indicate that all items are valid, while the reliability test shows a Cronbach’s Alpha value of 0.870, indicating high internal consistency. Assumption tests, including normality and linearity tests, confirm that the data meet the requirements for parametric analysis. Hypothesis testing using simple linear regression reveals a very strong and statistically significant relationship between Time Management and Work–Family Conflict (R = 0.906; p < 0.01). The findings indicate that Time Management contributes significantly to variations in Work–Family Conflict. Effective time management is associated with lower levels of work–family conflict. Therefore, improving time management skills may help reduce work–family conflict and enhance individual well-being.